Meningkatkan Motivasi Belajar Anak Usia 5-6 Tahun Melalui Program Kerjasama Guru Dan Orang Tua Di TPQ Baitussalam - Alfiah , Nurul; Priyanti , Nita; Priyanti , Nina Yuminar (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
Nuru Alfiah. Increasing the learning motivation of children aged 5-6 years through the Teacher and Parent Collaboration Program at TPQ Baitussalam, South Bekasi. Bekasi: Bekasi: Sekolah Tinggi Ilmu Keguruan dan Ilmu Pendidikan Panca Sakti Bekasi. 2024. This research aims to determine the increase in learning motivation of children aged 5-6 years through the Teacher and Parent collaboration program at TPQ Baitussalam Bekasi. This research uses the Classroom Action Research Method (PTK) which uses the model from Kemmis & Taggart. This research method aims to improve children's learning motivation and parents' thoughts in motivating children's learning. During the research, this classroom action research was carried out in two cycles to see an increase in children's learning motivation, where each cycle consisted of planning activities, action implementation, observation and reflection. The subjects of this research were 10 children aged 5-6 years. This research was carried out at the Tpq Baitussalam located in Bekasi. The data collection technique used in this research was complete participant observation, which means that in carrying out data collection, the researcher was fully involved in the learning. The research results show that through the teacher and parent collaboration program, children aged 5-6 years can increase the learning motivation. Classroom action research was carried out after seeing the pre-cycle situation, namely 45% had not developed yet. Cycle I showed that 60% of children developed as expected and in cycle II there was a very significant increase, namely 86% of children whom developed very well. This research provides an important meaning in choosing the right way to increase early childhood learning motivation through collaboration between teachers and parents.